Produção de xilitol por linhagens de leveduras do gênero Cyberlindnera - Rafael Marques de Souza (2019)
In Brazil, by-products from the agricultural sector are examples of lignocellulosic materials that can be used as promising raw materials for biotechnological applications, such as the production of second-generation ethanol and xylitol. The biomass consists of three main components, and it is from the hemicellulosic fraction that are liberated, after pretreatment, fermentable sugars such as D-xylose that can be converted to xylitol. This compound is a high added value product with emphasis on food and pharmaceutical use. Among the xylitol-producing microorganisms, yeasts are identified as the best, and the strains of the genera Candida, Meyerozyma, Spathaspora and Cyberlindnera are the most extensively studied for this property. The need for new strains or species of xylitol-producing yeasts has increased in recent years, especially strains that are capable of producing this compound from lignocellulosic residues. In this sense, this work had as proposal to evaluate the production of xylitol by seven strains of yeasts of the genus Cyberlindnera by means of D-xylose conversion tests in complex medium and in medium containing hemicellulosic sugarcane bagasse hydrolyzate (HSBH). Initially, cultures were made in 250 mL Erlenmeyer flasks containing 100 mL of YPX medium (D-xylose 50gl-1, 20gl-1 peptone, yeast extract 10gl-1) with initial inoculums of 1 gL-1 and 3 gL-1 of cells. The strain UFMG-HMD 19.1 was the best producer of xylitol in both initial inocula, and with inoculum of 3 gL-1, the production of this compound was 29.2 gL-1 (Yp / s = 0.624 gg-1; Qp = 0.487 gL-1h-1). This lineage was selected, along with the lines UFMG-HMD 8.2 and YFGJ 79F-b, for the cultivation in HSBH. The assays were conducted in 125 ml Erlenmeyer flasks containing 50 ml of culture medium and using the growth conditions referring to the best results obtained with the initial inoculum of 3 gL-1 with the YPX medium. Under these conditions, the best results for the production of xylitol were obtained by the strain UFMG-HMD 8.2, whose production was 15.22 gL-1 of xylitol with xylose consumption of 54.95%, xylose conversion factor in xylitol of 0.603 gg-1, yield of 0.105 gL-1h-1 and efficiency of 65.75% in 144 hours of fermentation. Therefore, this lineage has the potential to be used in industrial processes to obtain xylitol from lignocellulosic residues.